'Entamoeba histolytica' identified by stool microscopy from children with acute diarrhoea in Peru is not E. histolytica. (January 2020) - Quispe-Rodríguez, Gabriel H; Wankewicz, Alyssa A; Luis Málaga Granda, José; Lewis, Ben; Stockert, Kassi; Clinton White, A
Entamoeba histolytica is a rare but feared pathogen owing to its related morbidity and mortality. Physicians in an ambulatory clinic in Cusco noted frequent reports of E. histolytica diagnosed by microscopy. Other non-pathogenic species of Entamoeba have an identical microscopic appearance. To determine whether the organisms were actually E. histolytica, faecal specimens from children aged six months to three years with diarrhoea were tested by a species-specific ELISA for E. histolytica antigen. Although 19/73 patients (26.0%) were presumptively diagnosed with amoebiasis based on microscopy, none were confirmed by ELISA. Most cases diagnosed as E. histolytic by microscopy in Peru are not infected by the pathogenic species and are probably colonised by non-pathogenic amoeba such as Entamoeba dispar.